Cultural Explanations for Academic Underachievement of Ethnic Minority Students at Secondary Level in Vietnam - Tran, Tien Ngoc (Advances in Social Sciences Research Journal, 2017)
Ethnic minorities in Vietnam face more disadvantages in accessing infrastructure, financial services, healthcare, and modern technology. In education, their children also have lower educational achievements as well as higher dropout and class repeating rates in comparison with their majority peers. This paper explores the reasons for educational underachievement of ethnic minority students at the secondary level in Lam Dong Province, Vietnam, through an investigation of factors related to the cultural aspects including cultural values, norms, beliefs, and practices towards education. It, furthermore, looks for the explanations of the gaps between the educational achievement of ethnic minority and majority children. The study was conducted in Lam Dong Province, Vietnam, through qualitative approaches with in-depth interviews, discussions observations and informal dialogues in 2010. Additional fieldwork was done in 2015 to provide a more comprehensive understanding and a fuller description of the issue. The findings show that ethnic minority students do not have sufficiently conducive conditions for high educational performance. They undergo the misconceptions and stereotyping from their majority peers for their physical and cultural differences. Furthermore, students do not have positive attitudes towards their learning and lack educational purposes. They hardly believe that education can be of any value or relevant to their future success. Ethnic minority students also lack sufficient encouragement from their parents and are encouraged to drop out of school to help their families in farming or to get married early. The findings confirm that cultural factors do have some impacts on the academic achievement of ethnic minority students.